Lichen planus like keratosis: little known and misleading etiology of pigmented skin lesion - Asermouh, Marwa; Khabba, Chaimae Ait; Mehsas, Zoubida; Derqaoui, Sabrine; Znati, Kaoutar; Meziane, Mariame (International Journal of Research in Dermatology, 2023)
Benign lichenoid keratosis is a rarely described entity in the literature. It is believed to correspond to a process of clearance of a solar lentigo or a seborrheic keratosis that must be confirmed on histology. The clinical and dermoscopic presentations are very variable from one subject to another and according to the stage of progression. In our case, its localization on the umbilicus with a grayish-black clinical aspect and a doubtful dermoscopy is not only original, but led us to wrongly think of a malignant tumor and to perform an anatomopathological examination that helped to re-establish the diagnosis.